MicroRNA-29b-3p Promotes Human Retinal Microvascular Endothelial Cell Apoptosis via Blocking SIRT1 in Diabetic Retinopathy - Zeng, Yong; Cui, Zekai; Liu, Jian; Chen, Jiansu; Tang, Shibo (Frontiers in Physiology, 2020)
Background Diabetic retinopathy (DR) is a main complication of diabetes mellitus (DM). Recent studies have implicated microRNAs in human retinal microvascular endothelial cell (HRMEC) dysfunction. In this study, we aim to investigate the apoptotic promotion of miR-29b-3p by blocking SIRT1 in HRMEC for DR situation. Method Blood samples were obtained from DR patients and controls. Dual-luciferase reporter assay using HEK-293T cells was performed to show the direct interaction of miR-29b-3p and the 3′UTR of SIRT1. HRMECs were exposed to 5.5 mmol/L of glucose (normal control), 5.5 mmol/L of glucose and 24.5 mmol/L of mannitol (osmotic pressure control), 30 mmol/L of glucose [hyperglycemia (HG)], 150 μmol/L of CoCl2 (hypoxia), and 30 mmol/L of glucose plus 150 μmol/L of CoCl2 (HG-CoCl2). To identify the regulating relationship between miR-29b-3p and SIRT1, HRMECs were transfected with miR-29b-3p mimics/inhibitors or their negative controls. SRT1720 was used as a SIRT1 agonist. Cell viability was assessed with the cell counting kit-8 (CCK-8) assay, and apoptotic cells were stained by one-step terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay kit. Gene and protein expression were assayed by quantitative real-time reverse transcriptase-PCR (RT-qPCR) and western blotting separately. Result MiR-29b-3p was upregulated to 3.2-fold, and SIRT1 protein was downregulated to 65% in DR patients. Dual-luciferase reporter assay showed the direct interaction of miR-29b-3p and SIRT1. HRMECs were identified as >95% positive for CD31 and von Willebrand factor (vWF). MiR-29b-3p and Bax/Bcl-2 ratio was upregulated, whereas SIRT1 was downregulated in HRMECs in the HG-CoCl2 condition. Decreased cell viability and upregulated apoptosis were also found in HRMECs of the HG-CoCl2 condition. Upregulated miR-29b-3p decreased the expression of SIRT1 and increased the ratio of Bax/Bcl-2, whereas downregulated miR-29b-3p increased the expression of SIRT1 protein and downregulated the ratio of Bax/Bcl-2. SRT1720 rescued miR-29b-3p-induced HRMEC apoptosis via upregulating the expression of SIRT1 protein. Conclusion The dysregulation of miR-29b-3p/SIRT1 is a potential mechanism of HRMEC apoptosis in DR. MiR-29b-3p/SIRT1 may be a potential therapeutic target for DR.